2004
DOI: 10.1039/b316616c
|View full text |Cite
|
Sign up to set email alerts
|

One-step immobilization of aminated and thiolated DNA onto poly(methylmethacrylate) (PMMA) substrates

Abstract: Direct immobilisation of modified DNA oligonucleotides (aminated or thiolated) onto a plastic substrate, poly(methylmethacrylate), (PMMA) is described. Using the methyl esters present on non-modified PMMA, it was possible to establish a covalent bond between the electron donor of a DNA probe and the C terminal ester of the PMMA substrate. Since the procedure consists of a single brief wash in isopropanol or ethanol, the procedure is simple and environmentally friendly. The new immobilization strategy was chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 33 publications
1
110
1
2
Order By: Relevance
“…However, the high autofluorescence of standard polymeric materials is not compatible with a highly sensitive detection method that employs fluorescent targets. Plastic microarray hybridizations compatible with fluorescent dyes have been developed previously (5,6,13). However, these investigators reported only hybridizations with labeled oligonucleotides, and the specific hybridization signal-to-background ratios were relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high autofluorescence of standard polymeric materials is not compatible with a highly sensitive detection method that employs fluorescent targets. Plastic microarray hybridizations compatible with fluorescent dyes have been developed previously (5,6,13). However, these investigators reported only hybridizations with labeled oligonucleotides, and the specific hybridization signal-to-background ratios were relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…The only other reported study of room temperature hybridization on plastic supports was performed using a 16-h protocol, and the hybridization signal-to-background ratios obtained were low (approximately 10) (4). Others have performed hybridization experiments on plastic supports at 30 to 65°C, requiring special heating devices to carry out the hybridizations (5,6,15,17,23,25). In addition, stability tests demonstrated that when stored in a vacuum desiccator, the chemically activated plastic slides were stable for at least 10 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…34 In this case, the methyl ester groups at the surface of PMMA undergo a nucleophilic attack by the amine groups and this gives directly an amide linkage upon elimination of methanol. Although this method is simple, the authors not only indicate a high variability in their results, but Target #2 59-TAGGACACTCATAAT-39 59-Cy5 also report that the ''coupling reactions fail occasionally'' and this may be due to the high pH employed in the reaction as DNA may undergo hydrolysis.…”
Section: Surface Chemistry and Immobilization Of Dna On Poly(cyclic Omentioning
confidence: 99%
“…For the latter method, generally aminated or thiolated oligonucleotides are used [3][4][5]. The key problems to overcome for the preparation of DNA array based sensors or chips are the attachment of functional groups to the solid surface, the synthesis of oligonucleotides containing reactive groups, the spacial distribution of the DNA oligomers, and the detection of hybridization with complementary strands.…”
mentioning
confidence: 99%